Metoda microteachingu w edukacji przyszłych nauczycieli - Marciniak , Mateusz; Forecka-Waśko , Katarzyna; Kasprzak , Michalina; Jaskulska , Sylwia (Studia Edukacyjne, 2024)
The education of pre-service teachers is a significant process for developing educational systems worldwide. The article aims to discuss microteaching as a teacher training method. It presents a case study result: an analysis of interviews with students after microteaching implementation during the courses “Drama Method for Social Inclusion in Teaching Practices” and “Creative Arts for Social Inclusion” (offered at the Faculty of Educational Studies of Adam Mickiewicz University, Poznań, Poland as the part of the CARE/SS project). Conclusions lead to understanding the potential of microteaching for stimulating collaborative processes and deep teacher role understanding.